THE DARK SIDE OF FAME - Alexandropoulou, Anna-Maria; Riga, Lydia (Open Schools Journal for Open Science, 2025)
Hollywood is often perceived as the land of dreams, where fame and success are attainable for those who dare. However, behind the glamour and flashing lights lies a much darker reality. This report examines the hidden struggles associated with fame, including the mental and emotional toll on young celebrities, the exploitation within the entertainment industry, and the cultural obsession with scandals. Through real-life cases and movements such as #MeToo, this paper explores the human cost of celebrity culture.